Central Portuguese Doctors’ agreement with the “Ten Commandments for patient-centred treatment” - Santiago, Luiz Miguel de Mendonça Soares (2019)
Background. The “Ten Commandments for patent-centred treatment” suggest a diﬀerent approach to therapy. Objectves. To ascertain the level of agreement with the “Ten Commandments for patent-centred treatment” by physicians in Central Portugal, exploring diﬀerences by age group, sex and medical speciality. Material and methods. An online questonnaire in September of 2016, sent to doctors registered in the Central Regional Secton of the Portuguese Medical Associaton, with weekly reminders to non-respondents. The English wording was translated to Portuguese, a questonnaire with a four-grade answer was created and its reliability determined. Variables such as sex, age group and medical specialty were considered. Descriptve and inferental statstcs were performed. Results. A representatve yet convenient sample of 811 doctors partcipated. Their descripton is as follows: ≤ 35 years n = 203, ≥ 36 and ≤ 55 years n = 217 and ≥ 56 years n = 373, women n = 391 (49.2%), General Practce/Family Medicine (GP/FM) n = 301, medical specialty n = 303 and medico-surgical specialty n = 173. By medical specialty, for commandment 1, there is higher prevalence of “Disagree/Completely Disagree” in the GP/FM specialty (p < 0.001). By gender, for commandment 1, women vs men doctors “Disagree/Completely Disagree” proporton of 11.7% vs 6,4% (p = 0.003). For the younger age groups, there is a greater proporton of “Disagree/Completely Disagree” for Commandment 1 (p = 0.016), for Commandment 4 (p = 0.007), for Commandment 6 (p = 0.001), for Commandment 7 (p = 0.001) and for Commandment 8 (p = 0.020). Conclusions. There is vast agreement with the “Ten Commandments for patent-centred treatment” in central Portugal. For Commandments 1, 3 and 6, the proporton of “Disagree/Completely Disagree” is higher than for the remaining. There is a need for future investgatons to explain the present results.